2013
DOI: 10.1542/peds.2013-0296
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Adiposity in Metabolically Healthy Overweight and Obese Youth

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Obesity is associated with cardiometabolic risk factors and chronic conditions, such as type 2 diabetes. However, a proportion of overweight and obese youth remain free from cardiometabolic risk factors and are considered metabolically healthy. WHAT THIS STUDY ADDS:This study provides insight into the determinants of cardiometabolic risk factors and the concept in health promotion of "fitness versus fatness." Hepatic lipid accumulation and not fitness level appears to drive cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 40 publications
2
56
1
1
Order By: Relevance
“…In accordance previous literature in youth 29,50,51 , we suggest to exclude waist circumference among the criteria to be considered for MHO.…”
Section: Recommendationsupporting
confidence: 78%
See 1 more Smart Citation
“…In accordance previous literature in youth 29,50,51 , we suggest to exclude waist circumference among the criteria to be considered for MHO.…”
Section: Recommendationsupporting
confidence: 78%
“…In addition, a summary of the characteristics of these studies is shown in Table 2. Surprisingly, 75% of the studies focused exclusively on women 20-28 and only 25% focused on both women and men (no study was focused only in men) [29][30][31] .…”
Section: Overall Description Of the Studies Reviewedmentioning
confidence: 99%
“…A large cross-sectional study among Spanish adults [23] provided evidence that PA is one of the main factors responsible for a healthy phenotype among the obese. Only few studies published results for adolescents and these showed no association between PA and metabolically healthy obesity [22, 52]. Further research in children is needed, as there are no studies on metabolically healthy obesity in children.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically healthy obesity is apparently associated with lower levels of adiposity in youth [22, 23] and a high level of physical activity (PA) in adults [22, 23]. Increased PA and cardiorespiratory fitness are also believed to attenuate the risk of cardiovascular disease, type 2 diabetes, and MS, independent of weight status [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is fair to say that we are just beginning to understand this phenomenon. Most authors refer to the number of cardiometabolic risk factors when applying or introducing a definition of MHO, and prevalence of MHO in obese youths is estimated to be between 4.2% and 25% [10,11]. The birth weight and obesity rebound during early infancy have been suggested as influencing factors.…”
mentioning
confidence: 99%